Nilai-nilai Pendidikan Karakter dalam Tradisi Tabot pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) di Madrasah Aliyah Negeri - Rossi Delta Fitrianah (Indonesian Journal of Character Education Studies, 2024)
Background: Character education is a crucial aspect of shaping students' personalities, particularly by introducing local cultures rich in moral values. The Tabot tradition, which has developed in Bengkulu, is a cultural heritage that embodies noble values and is a valuable source of learning-especially within the Islamic Cultural History (SKI) subject. Objective: This study aims to identify the forms of character education values embedded in the Tabot tradition as taught in the SKI subject at MAN 1 Bengkulu City. Method: This research utilized a case study approach. It was conducted in 2021 at MAN 1 Bengkulu City, involving 11th-grade students as research subjects. Data collection techniques included observation, interviews, and documentation. Data analysis followed the process of data reduction, data presentation, conclusion drawing, and verification. Data validity was tested using source and time triangulation techniques. Result: The study found that (1) Character values in the Tabot tradition are integrated into the existing curriculum; (2) These values are also embedded through the hidden curriculum; and (3) character values are further reflected in students' extracurricular activities. Conclusion: The Tabot tradition can be an effective learning medium for instilling character education values through formal and non-formal educational pathways in madrasahs. Contribution: This research contributes as a scientific source of information for teachers and education practitioners on integrating local wisdom-based character education values, particularly those found in the Tabot tradition, into the Islamic Cultural History subject in Islamic senior high schools.